Flotation-Spectrophotometric Determination of Traces of Lead Ion - NEKOUEI, F.; PARHAM*, H. (Asian Journal of Chemistry, 2009)
A simple, fast, reproducible and sensitive method for the flotation- spectrophotometric determination of Pb2+ is reported. The method is based on the ternary ion-association of Pb2+, xylenol orange (XO) and cetyltrimethylammonium bromide (CTAB) which is floated at interface of aqueous phase and n-hexane by shaking the separating funnel. By discarding the aqueous solution (the more dense phase) the adsorbed ion associate (Pb2+-XO)-CTA+ on to the wall of a separatory funnel was extracted and dissolved in a small volume of methanol solvent and absorbance was measured at 583 nm. The apparent molar absorptivity (ε) of the ion associate was determined to be 6.13 × 104 mol-1 cm-1. The calibration curve was linear in the concentration range of 0.2-5.0 μg mL-1 of Pb2+ with a correlation coefficient of 0.9996. The limit of detection (LOD) is 0.0427 μg mL-1. The relative standard deviation (RSD) at 0.6 and 1.5 μg mL-1 of lead were 2.478 and 1.040 % (n = 8), respectively. The method was applied for measuring the amount of lead in blood and soil samples.